PELATIHAN PEMBUATAN RUNNING TEXT BERBASIS MATRIX DISPLAY LED DENGAN MENGGUNAKAN HD-U6A - Waluyo, Catur Budi (Sekolah Tinggi Teknologi Adisutjipto, 2018)
The rapid development of electronics technology requires the availability of human resources who have sufficient skills. Students as partners in community service, have participated in LED-based running text design training. The main goal in this community service activity is to improve the skills in the field of electronics and human resources. Targets achieved at this stage is to improve the ability to design and make the program of running text based Led matrix display. The enhancement of designing capability is done through Led-based running text training activity in software and hardware. This activity has been able to achieve the expected goals and targets so that partners can make running text with a more affordable cost.